Pesan Al-Quran dalam Menyikapi Berita Hoax: Perspektif Dakwah di Era New Media - Mujib, Abd. (Jurnal Komunikasi Islam, 2018)
The rapid development of social media in the contemporary era, has given birth to the phenomenon of hoax, which is very disturbing for society. This is because the consequences of hoax messages are slanderous and attempts to disunite social groups. In response to this, the role of Islamic preacher (da’i) in conveying the message of the Qur'an regarding the importance of providing accurate information is necessary. The da'is are obliged to convey the truth according to al-Qur'an to ummah and to provide them a clear understanding in addressing the hoaxes news. Thus, the hoaxes news that often encourage social, political, and religious conflicts in the society can be resolved quickly and appropriately.